As diretrizes curriculares nacionais para educação: das relações étnico-raciais e formação docente curso de história da Universidade Federal do Pará - SILVA JÚNIOR, Elton Luis da (Universidade Federal do Pará, 2020)
This study analyzes the National Curricular Guidelines for the Education of Ethnic-Racial Relations - DCNERE and the process of teacher education of History, Federal University of Pará, Campus Bragança. The study presents a qualitative approach with the application of documentary research (Pedagogical Project of the History Course). Through the PPC of the Course of History the present work investigates how the Nuclei of Disciplines of the Course of History contemplate the ethnic-racial relations in the Teaching of History. The results reveal that the contents related to ethnic-racial relations are inserted minimally in the curriculum in which the teacher of History and, in a certain way, fulfills the formal requirement in the legislation. We conclude that the space reserved for Europe is still privileged through historiographic knowledge as the guiding thread that weaves the paths of Western historiography, which makes it difficult to discuss racism and its ramifications in the school context.